TEACHING METHODS USED BY STUDENTS OF DEPARTMENT OF ENGLISH LANGUAGE EDUCATION OF UIN AR-RANIRY IN TEACHING ENGLISH AT ENGLISH COURSE - Dara Fitria Munzaki; Lilis Suadah; Risdaneva Risdaneva (Universitas Islam Negeri Banda Aceh, 2016)
Learning can take place in school, course, and community. There are some differences of teaching at school and course, such as teaching methods used. It is one of the most important elements in teaching. Teaching method is used to help the learners to gain the knowledge and help them to achieve their learning targets. Therefore, this research focused on teaching methods that were used by English Education Department students in UIN Ar-Raniry in teaching grammar at English courses. The purposes of this research were to identify which methods were used in teaching grammar at courses and to describe the teaching techniques that were applied in classroom. The participants were five English Education students who have been teaching English at English courses. They were selected using purposive sampling with a consideration that they have completed Teaching Method, Micro Teaching, and Teaching Practice (PPL) subjects in their previous semesters. This research was conducted by using qualitative descriptive and two techniques for collecting data namely observation and interview. Based on the research findings, writer found that all of the selected teachers used Grammar Translation Method (GTM) as the main teaching method which was sometimes combined with some techniques of other methods such as Direct Method, Communicative Language Teaching (CLT), and Bilingual Method.